Management Strategy for the Development of Pesantren's Hidden Curriculum in Schools - Carnawi, Carnawi; Zamzami, Zamzami; Nasoha, Ahmad Muhamad Mustain; Muarif, Yahya Zaenul; Abdullah, Imam (DINIKA : Academic Journal of Islamic Studies, 2024)
The curriculum at SMPIQu Al-Bahjah Cirebon faces a challenge in integrating the formal, official curriculum with the non-formal pesantren (Islamic boarding school) curriculum. This disconnect has resulted in the pesantren curriculum becoming somewhat "hidden" or underrepresented. The core issue addressed in this research is how to design, implement, and evaluate the development of this hidden pesantren curriculum. Using a qualitative research method, the study draws from both primary and secondary data, collected through observation and interviews. The findings reveal a five-step approach to developing the hidden curriculum. Implementation is achieved through structured activities such as work meetings, scheduling academic activities, enhancing the management information system (SIM), improving teaching staff and student resources, strengthening students' morals, and increasing proficiency in foreign languages. The evaluation process includes supervision, regular meetings, audits, and reporting. The study concludes that effective curriculum development hinges on a morals and creed-based education, improved administrative and management systems, optimization of media as a development tool, and active participation in competitions and events. This research contributes to the formulation of strategies for developing the hidden pesantren curriculum, offering practical benefits for all stakeholders involved.